2004
DOI: 10.1097/01.ju.0000127743.80759.7a
|View full text |Cite
|
Sign up to set email alerts
|

Alfuzosin Once Daily Facilitates Return to Voiding in Patients in Acute Urinary Retention

Abstract: Alfuzosin (10 mg) once daily significantly improved the rate of successful TWOC in patients with AUR related to BPH, even in elderly patients and those with a large drained volume who were at increased risk for TWOC failure. This should contribute to decrease the morbidity and mortality associated with emergency surgery and avoid the discomfort and potential morbidity associated with an in situ catheter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
3
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 14 publications
3
69
3
2
Order By: Relevance
“…TWOC can be attempted, although if hydronephrosis or renal impairment is present the patient should remain with indwelling catheter until surgery. 7 Although our patient had over 1000 mL of residual urine, which is a factor leading to a high probability of unsuccessful TWOC, 10 we still decided to pursue TWOC because he was under 65 years old and had good detrusor function. In patients with low-pressure, chronic urinary retention prostatectomy is in many cases unsuccessful as they fail to void completely after surgery and require long-term or clean intermittent self-catheterization.…”
Section: Discussionmentioning
confidence: 95%
“…TWOC can be attempted, although if hydronephrosis or renal impairment is present the patient should remain with indwelling catheter until surgery. 7 Although our patient had over 1000 mL of residual urine, which is a factor leading to a high probability of unsuccessful TWOC, 10 we still decided to pursue TWOC because he was under 65 years old and had good detrusor function. In patients with low-pressure, chronic urinary retention prostatectomy is in many cases unsuccessful as they fail to void completely after surgery and require long-term or clean intermittent self-catheterization.…”
Section: Discussionmentioning
confidence: 95%
“…The successful voiding rate was significantly higher in patients treated with alfuzosin than in those treated with placebo (62% versus 48%, resp. ; = 0.002) [7]. Various clinical trials have demonstrated that ABs, including tamsulosin and alfuzosin, are effective and safe in AUR management, with successful removal percentages that range from 48% to 70% [15].…”
Section: Discussionmentioning
confidence: 99%
“…The large randomized, double-blind, placebo-controlled alfuzosin in another AUR study investigated the impact of AB on the outcome of TWOC [7]. Three hundred sixty patients with a first episode of AUR-related BPH were randomized to receive 10 mg alfuzosin once daily or placebo for 2-3 days following catheterization [7]. The successful voiding rate was significantly higher in patients treated with alfuzosin than in those treated with placebo (62% versus 48%, resp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations